PENGARUH MEDIA MANIK-MANIK TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWAKELAS II SD - Dinda Kasturi; Sarah Fazilla; Husaini (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
This study aims to examine the effect of using bead media on students’ understanding of place value concepts in mathematics learning for second-grade elementary school students. The research employed a quantitative approach with a quasi-experimental method using a pretest-posttest control group design. The population consisted of all second-grade students at SD Negeri 1 Syamtalira Bayu, totaling 45 students, divided into an experimental group and a control group. Data were collected through pretest and posttest instruments designed to measure students’ conceptual understanding. The results showed that the average posttest score of the experimental group was higher than that of the control group, with a more significant improvement in learning outcomes. Statistical analysis using a paired samples t-test indicated a significant difference between pretest and posttest results. Therefore, the use of bead media is proven to be effective in improving students’ understanding of place value concepts in elementary mathematics learning.